A COMPARATIVE STUDY OF PQRST AND SQ3R STRATEGIES BASED ON THE TEXT TYPES UPON THE EIGHTH GRADE STUDENTS’ READING COMPETENCY AT SMPN 4 SINGARAJA - Komang Dedy Sandiarsa; Dewa Komang Tantra; Ni Made Ratminingsih (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2014)
This research aimed at investigating whether or not there is a different effect between PQRST and SQ3R strategies based on the text types upon the eighth grade students’ reading competency. This research was an experimental research with 2 X 2 factorial designs. The population was 6 classes (179 students) of grade VIII in SMPN 4 Singaraja in the academic year 2012/2013, in which 4 classes were sample of this research which was assigned into two groups, two classes with 60 students were PQRST strategy group, and two classes with 60 students were SQ3R strategy group determined by using a Multistage Random Sampling. The data were collected through reading comprehension test that were analyzed by using Statistical Two-Way ANOVA. The result shows that, first, FA = 31.533 with the significant value was 0.000 which was less than 0.5, therefore, there is a significance difference between the students who were taught by PQRST strategy than those who were taught by SQ3R strategy. Second, FAB = 2.624 with the significant value was 0.107 which was higher than 0.5, therefore, there is no interactional effect of teaching reading strategies (PQRST and SQ3R) and text types (narrative and recount) on students’ reading competency.